Meckel's Diverticulum in Adults: Surgical Concerns - Blouhos, Konstantinos; Boulas, Konstantinos A.; Tsalis, Konstantinos; Barettas, Nikolaos; Paraskeva, Aikaterini; Kariotis, Ioannis; Keskinis, Christodoulos; Hatzigeorgiadis, Anestis (Frontiers in Surgery, 2018)
Since Meckel’s diverticulum (MD) is rarely diagnosed in adults, there is no consensus on what type of procedure to be performed for symptomatic MD and whether to resect or not an accidentally discovered MD. Treatment of symptomatic MD is definitive surgery, including diverticulectomy, wedge and segmental resection. The type of procedure depends on: (a) the integrity of diverticulum base and adjacent ileum; (b) the presence and location of ectopic tissue within MD. The presence of ectopic tissue cannot be accurately predicted intraoperatively by palpation and macroscopic appearance. When present, its location can be predicted based on height-to-diameter ratio. Long diverticula (height-to-diameter ratio >2) have ectopic tissue located at the body and tip, whereas short diverticula have wide distribution of ectopic tissue including the base. When indication of surgery is simple diverticulitis, diverticulectomy should be performed for long and wedge resection for short MD. When indication of surgery is complicated diverticulitis with perforated base, complicated intestinal obstruction and tumor, wedge or segmental resection should be performed. When the indication of surgery is bleeding, wedge and segmental resection are the preferred methods for resection. Regarding management of incidentally discovered MD, routine resection is not indicated. The decision making should be based on risk factors for developing future complications, such as: (1) patient age younger than 50 years; (2) male sex; (3) diverticulum length greater than 2 cm; and (4) ectopic or abnormal features within a diverticulum. In this case, diverticulectomy should be performed for long and wedge resection for short MD.